New discovery of late early ordovician graptolites and discussion on stratigraphic sequence of paleozoic sediments in the Dinh Ca - Trang Xa Section, Vo Nhai Disctrict, Thai Nguyen Province, Northeast Vietnam - Hung*, Nguyen Huu; Minh, Nguyen Trung; Hung, Doan Dinh; Hung, Nguyen Ba (Vietnam Journal of Earth Sciences, 2017)
Sandstone, quartzitic sandstone rhythmically interbedded with siltstone, calcareous siltstone and cherty shale are largely exposed in the Dinh Ca - Trang Xa area, Vo Nhai District, Thai Nguyen Province, NE Vietnam. In previous studies, they were described as Mo Dong or Than Sa Formations (Middle-Upper Cambrian). The graptolite faunas newly discovered from the Dinh Ca Market - Na Mo - Dong Bo cross section are composed of Expansograptus urbanus (Monsen), Expansograptus abnormis (Hsu), Tetragraptus quadribrachiatus (Hall), T. approximatus Nicholson, T. pacificus Ruedemann, T. decipiens T.S. Hall, Schizograptus sp., belonging to the quadribrachiatus Biozone, indicating Floian Stage or late Early Ordovician. This serves as the basis for age determination and for establishing new lithostratigraphic units termed as the Dinh Ca Formation (O1 dc) and the Ba Nhat Member. The stratigraphic sequence of Paleozoic sediments in the Dinh Ca - Trang Xa area is also discussed in this paper. References Bergstöm S. M., Löfgren A., and Maletz J., 2004. The GSSP of the Second (Upper) Stage of Lower Ordovician Series: Diabasbrottet at Hunneberg, Province of Västergӧtland, Southwestern Sweden. Episodes, 27(4), 265-272. Bergstöm S. M., Chen X., Gutierrez-Marco J.C., and Dronov A. V., 2008. The new chronostratigraphic classification of the Ordovician System and its relations to major regional series and stages to δ13C chemostratigraphy. LETHAI, 42(1), 97-107. Dovjikov, A. E. (ed) et al., 1965. (1971 in Vietnamese). The Geology of the Northern part of Vietnam. Geological Survey of Vietnam, Ha Noi, 583p. Doan Ky Thuy (Ed.), 1976. Geologyof the Lạng Sơn sheet (F-48-XXIII), 1:200.000 scale. Housed in the Central of Geological Information and Archives (in Vietnamese), Ha Noi. Doan Ky Thuỵ (Ed.), 2000. Geology and mineral resources of the Lạng Sơn sheet (F-48-XXIII), 1:200.000 scale. Published by Department of Geology and Minerals of Viet Nam (in Vietnamese with English summary), Ha Noi. Le Duy Bach, 1985. Structure and formation stages of Viet Nam in the tectonic framework of SE Asia. Abstract of PhD Dissertation (in Russian). The National Library of Viet Nam, 31 Trang Thi Street, Ha Noi. Mansuy H., 1908. Contribution à la carte géologiques de l’Indochine. Paléontologie, 73pp., Ha Noi. Nguyen Van Liem, 1978. On the Carboniferous system in North Viet Nam (in Vietnamese). Journal of Biology-Geosciences, 16(3), 78-85. Patte E., 1927. Études géologiques dans l’Est du Tonkin. Bull. Serv. Géol. Indoch., vol. XVI, fasc. 1, 314pp, Ha Noi. Pham Dinh Long (Ed.), 1968. Geology of the Tuyen Quang sheet (F-48-XXII), 1:200.000 scale. Housed in the Central of Geological Information and Archives. Ha Noi (in Vietnamese). Pham Dinh Long, Hoang Xuan Tinh, Phan Viet Ky, 1981. Some main features of regionalgeology of Northeast Viet Nam. Mapping, 48, 4-19, Ha Noi. Pham Kim Ngan, 1975. Some biostratigraphical sections of the Lower Paleozoic of North Viet Nam. Collections of works onstratigraphic studies in Viet Nam, 40-54. Science and Technics Publishing House (in Vietnamese), Ha Noi. Pham Kim Ngan, 1982. Some research results of the Cambrian and Ordovician biostratigraphy in Viet Nam. Geology and Minerals, 1, 7-17. Published by Institute of Geology and Mineral resources (in Vietnamese with English summary), Ha Noi. Saurin E., 1956b. Lexique stratigraphique international. Vol. III, fase, 6a: Indochine. Centre National de la Rech. Scient., 140p. Paris. 1970: published by Science and Technics Publishing House, 222pp. (in Vietnamese), Ha Noi. Tong Duy Thanh, Vu Khuc (Eds.), 2011. Stratigraphic units of Viet Nam.Vietnam National University Publishing House, 526pp, Ha Noi. Tran Van Tri, Ta Hoang Tinh, Phan Son, Le Duc An, 1964. On the Lower Paleozoic sediments in the Than Sa area. Journal of Geology, series A, 37, 6-11 (in Vietnamese with Russian summary), Ha Noi. Tran Van Tri, Vu Khuc (Eds.), 2011. Geology and Earth resources of Viet Nam. Publishing House for Science and Technology, 645pp, Ha Noi. Xu Chen, Strig M. Bergström, Yuan-Dong Zhang and Jun-Xuan Fan, 2009. The base of the Middle Ordovician in China with special reference to succession at Hengtan near Jiangshan, Zhejiang Province, Sothern China. LETHAI, 42, 218-231.